Participatory approaches to investigate breeding objectives of livestock keepers - Duguma, G.; Mirkena, T.; Haile, Aynalem; Iñiguez, L.; Okeyo Mwai, Ally; Tibbo, Markos; Rischkowsky, Barbara A.; Sölkner, Johann; Wurzinger, Maria (2010)
There are distinct breeds suitable for diverse purposes in the different production environments or ecological zones. Farmers in different production systems have different trait preferences and the strategies followed by them are also as diverse as the agro-environments within which they operate. In order to design a viable breeding plan, farmers’ preferences for the different traits need to be investigated.